Android Based Tire Patch Search - Sukri Sukri; Ramadhan Putra; Wita Yulianti (Program Studi Teknik Komputer, Fakultas Teknik. Universitas Serambi Mekkah, 2021)
The number of motorized vehicles continues to increase, this will be directly proportional to the number of people who experience motorcycle damage when driving on the highway, such as leaking tires or burst tires. For motorists who do not know the surrounding area when a motorcycle tire is damaged, of course it will be difficult to find the nearest tire patch. In this study, an Android application will be developed to map and find the location of motorcycle tire patches in Bukit Raya District. This application will provide location-based services to users. With this application, users will get information in the form of a map showing the location of the nearest tire patch. Based on the test results, the tire patch location mapping application that was built is able to display the locations of the tire patches along with information on the travel route from the user's location to the nearest selected tire patch location. This application was developed on the Android operating system because Android provides an open platform for developers to create their own applications and Android is one of the operating systems that are widely used by smartphones that are growing rapidly now. This application is expected to help users who want to find the location of the tire patch along with information from the tire patch and the closest route to the tire patch location so that it is more efficient in terms of time